2011
DOI: 10.1074/mcp.m110.000042
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Unbiased Proteomic Approach to Detect the Reactivity of Cerebrospinal Fluid in Neurological Diseases

Abstract: Neurodegenerative diseases, such as multiple sclerosis represent global health issues. Accordingly, there is an urgent need to understand the pathogenesis of this and other central nervous system disorders, so that more effective therapeutics can be developed. Cerebrospinal fluid is a potential source of important reporter molecules released from various cell types as a result of central nervous system pathology. Here, we report the development of an unbiased approach for the detection of reactive cerebrospina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 90 publications
0
28
0
Order By: Relevance
“…Increased CRMP2 levels were detected in cerebrospinal fluids from patients with MS. Phosphorylated CRMP2 levels were reported to be upregulated in human brain sections containing chronic, active MS lesions and plaques compared with the absence of such reactivity in normal brains post-mortem [157]. Using a well-established animal model of MS, experimental autoimmune encephalomyelitis, which mimics many of the pathophysiological hallmarks of MS, Petratos et al showed that CRMP2 is phosphorylated and hence inhibited during the progression of experimental autoimmune encephalomyelitis in degenerating axons [68].…”
Section: Targeting Crmp2 In Sensory and Motor Neuron Disordersmentioning
confidence: 99%
“…Increased CRMP2 levels were detected in cerebrospinal fluids from patients with MS. Phosphorylated CRMP2 levels were reported to be upregulated in human brain sections containing chronic, active MS lesions and plaques compared with the absence of such reactivity in normal brains post-mortem [157]. Using a well-established animal model of MS, experimental autoimmune encephalomyelitis, which mimics many of the pathophysiological hallmarks of MS, Petratos et al showed that CRMP2 is phosphorylated and hence inhibited during the progression of experimental autoimmune encephalomyelitis in degenerating axons [68].…”
Section: Targeting Crmp2 In Sensory and Motor Neuron Disordersmentioning
confidence: 99%
“…The presence in the CSF of autoantibodies and the identification of the immunogenic antigens have been investigated with SERPA also in some neurological disease, including multiple sclerosis, in which several antigenic candidates have been identified (Almeras et al, 2004;Gini et al, 2008;Menon et al, 2011). An early inflammatory phase has been postulated in several movement disorders, such as PD, and in the hyperkinetic movement disorders (HMDs) characterized by involuntary movements (Sanger et al, 2010).…”
Section: Immune Proteomicsmentioning
confidence: 98%
“…An alternative proteomics approach for CSF investigation might be the serological proteome analysis (SERPA) (De Monte et al 2008 ;Privitera et al 2013 ) that exploits the presence of autoantibodies in some neurological disease like multiple sclerosis (Menon et al 2011 ). In the SERPA approach, the autoantibodies present in the CSF of the patients are used to screen the proteome of the patient resolved by 2-dimensional electrophoresis in order to identify putative autoantigen/s.…”
Section: Proteomics Analysis Of Csfmentioning
confidence: 99%